Positive solutions for a class of fractional infinite-point boundary value problems - Wang, Y.; Liu, Lishan (SpringerOpen, 2018)
In this paper, we consider a class of fractional differential equations with infinite-point boundary value conditions. Under some conditions concerning the spectral radius with respect to the relevant linear operator, both the existence of uniqueness and the nonexistence of positive solution are obtained by means of the iterative technique.